Meat production and quality two unique properties of young camels - M. N. Bakkar; S. M. Basmaeil; A. A. Hamam (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2000)
Eighteen one-hump black (Majaheem) young camels were used to study growth rate and carcass percentage. The animals were selected and bought of similar age (about six months) and weight (around 150 kg). They were assigned randomly into three feeding groups. Each group was fed two types of rations: (A) concentrated pellets 18% crude protein at the rate of 1.5% CWT; and (B) one of three types of roughage: (a) alfalfa hay, (b) Rhodes grass hay, or (c) wheat straw treated with ammonia gas. Roughage was weighed and fed ad libitum. The experiment was ended when anirnals were about 14 months of age. Average body weights were 315, 298.8 and 291.4 kg for the three groups, respectively. Average daily gains for the three respective groups were 932, 803 and 767 g per day. Average carcass weights/kg (and carcass percentages) of each group were 180.6 (57.3%) for alfalfa, 170.7 (57.1%) for Rhodes and 168.1 (57.7%) for treated straw. Average forequarters weights/kg (and percentages to the carcass) were 98.9 (54.8%), 95.6 (56%) and 88.1 (52.4%) for the three groups, respectively. The hindquarters average weights/kg (and percentages) for the three respective groups were: 81,7 (45.2%), 75.1 (44%) and 80 (47.6%). Eight-year records (1986-1994) on carcasses of carnels, cattle and sheep were obtained from Riyadh Modem Slaughterhouse. The total number of animals killed was 3,891,301. Comparisons were made between the number of anirnals killed and the number of carcasses destroyed for each of the three species. It was found that on average for every carnel carcass destroyed 12 carcasses of cattle and 19 carcasses of sheep were destroyed. These results show clearly that camels produce the most hygienic meat for human consumption in comparison with cattle and sheep.